The Effect Of E-service quality, E-trust, and Price on Customer E-Loyalty mediated by Customer E-Satisfaction on Gen Z user of Lazada Application in Padang City: Pengaruh E-service quality , E-trust Dan Price Terhadap Customer E-Loyalty Yang Dimediasi Oleh Customer E-Statisfaction Pada Gen Z Pengguna Aplikasi Lazada di Kota Padang - Fira Rahmadani; Vidyarini Dwita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research was conducted with the aim of analyzing how electronic service quality, electronic trust, price influence customer loyalty, with customer satisfaction as a mediator in the Lazada application. The subjects of this research are Gen Z in Padang City. The sampling technique uses purposive sampling. The number of samples used was 180 respondents. Data was collected through a questionnaire with a Likert scale, then analyzed using SmartPLS 4.1 software. The results of this research show that electronic service quality, electronic trust, and price have a significant effect on electronic customer satisfaction and loyalty. However, electronic trust does not have a significant effect on electronic customer loyalty. E-customer satisfaction mediates the relationship between E-service quality, E-trust, price and e-customer Loyalty.